Self‐Diverting Acid System with Retarding Function for Heterogeneous Carbonate Reservoirs Stimulation. Issue 4 (12th March 2020) - Mao, Jincheng; Wang, Chen; Yang, Xiaojiang; Zhang, Heng; Zhang, Wenlong; Zhang, Chong; Lin, Chong
Abstract: Matrix acidization, an important technology for reservoir stimulation, has encountered challenges regarding heterogeneity. In addition to not achieving desired results, conventional acidization makes reservoir heterogeneity more prominent. In this study, we investigated the efficacy of a surfactant‐based functional acid system for uniform acidization in carbonate reservoirs. The two surfactants used in such acid systems are industrial initial products, which can be converted to a hydrochloride surfactant in hydrochloric acid. The conversion alters viscosity in reaction processes and can slow down reaction rates to allow for deeper rock penetration while at the same time forcing fresh acid into the untreated areas. The acid system can enhance well production considerably. It was found that the surfactant solution exhibited a relatively high viscosity at 90°C and is conducive to acid diverting. The retarding rate of the acid system was found to be up to 48%, allowing for deeper penetration. Parallel core flood testing indicates that the acid system exhibits superior diverting performance when compared to regular acid at 20 wt% HCl.